Legal Position of Land Certificate Custody by Notaries in Sale and Purchase Binding Agreements - Damayanti, Miranda; Labibah, Hanin Alya; Putri, Alfina Setyawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
In the practice of sale and purchase binding agreements (PPJB), the custody of land certificates by notaries is frequently carried out as a form of assurance for the parties before the completion of the sale and purchase process. However, this practice raises legal concerns regarding whether notaries act within their authority as public officials or as parties involved in civil law relationships through custody agreements. Since no specific regulation governs certificate custody by notaries, this issue requires further legal analysis. This study aims to examine the legal position of certificate custody by notaries in PPJB and analyze their responsibility for entrusted certificates. This research employs normative legal research using statutory and conceptual approaches. The legal materials consist of relevant laws and regulations, legal doctrines, and literature. The findings indicate that certificate custody by notaries in PPJB is generally considered a civil law act based on an agreement between the parties rather than an official obligation regulated under notarial law. Therefore, civil law provisions concerning custody (bewaargeving) apply to notaries' responsibilities for entrusted certificates. Notaries may be held liable for losses caused by negligence in managing the entrusted documents. This study concludes that notaries act as legal subjects in civil relationships during certificate custody practices. Clearer regulations are needed to ensure legal certainty and protection for all parties.